Assessment of microplastic contamination in the urban lower Chao Phraya River of Bangkok city, Thailand. (29th July 2022) - Ounjai, Khattiya; Boontanon, Suwanna Kitpati; Piyaviriyakul, Pitchaya; Tanaka, Shuhei; Fujii, Shigeo
Abstract: Rivers are one of the major pathways for the transportation of microplastics (MPs) from land-based sources to the ocean. However, there are only a few studies on MPs in freshwater environments, particularly in Asian countries. In this study, MP contamination in the Chao Phraya River in selected locations distributed throughout Bangkok, Thailand was investigated. MPs were collected using a Manta net with a mesh size of 335 μm. After digestion and distinction based on density, MPs were observed using a stereomicroscope, and polymer types were identified using Fourier Transform Infrared Spectroscopy. MP concentrations detected in the five sampling locations of the river water from upstream to downstream were 11, 35, 40, 15, and 4 particles/m 3, with an average concentration of 21±16 particles/m 3 . Most MPs were identified as either fragments or sheets/films. Polypropylene was the dominant polymer type. The number of MPs increases as their size decreases. Potential sources of MPs may include the degradation of single-use plastic products, especially containers and plastic packaging. MP concentrations and characteristics varied for different locations, indicating different sources and pathways of MPs in urban contexts. Further investigation on the different pathways of the transportation of MPs to river water from land-based sources is required. HIGHLIGHTS: Microplastic (MP) contamination in an urban river in Bangkok, Thailand, was investigated. Most MPs were identified as either fragments or films. Polypropylene was the dominant polymer type. There are different sources and pathways of MP contamination in urban rivers. The number of MPs increases as their size decreases. Graphical Abstract